Transformational Leadership on Performance of Selected Ethiopian Sport Federations - Samson Tadesse; Tesfay Haddera; Aschenaki Tessema (Pamukkale University, 2024)
Transformational leadership may not be positively and significantly affects the performance of sports federations, because sport organization unique nature is competitiveness and result-driven organization. The purpose of this study was to assess the impact of transformational leadership practices on the organizational performance of some Ethiopian sports federations. Cross-sectional design was used to collect transformational leadership and organizational performance variables. The study was conducted in Addis Ababa City Administration, Ethiopia. The data was collected from Ethiopian sports federations participants (n = 95). Transformational leadership as a predictor variable measured by multifactorial leadership questionnaire and sport federation performance was measured by Australian national Olympic sporting organizations effectiveness. SPSS version 26 was used to process the data; robust method of multiple regression analysis was used to analyze the data p < 0.05. The result of the study shows that idealized influence was statistically significantly predicted organizational performance (β = .26, p = .00). However, that inspirational motivation (β = .03, p = .54), intellectual simulation (β = .11, p = .12) and individualized considerations (β = -.05, p = .49) did not significantly predicted organizational performance. The finding of the study shows that transformational leadership idealized influence enhanced the performance of selected Ethiopian sports federations through inspiring trust, fostering commitment, promoting excellence, and cultivating a positive organizational culture. Ethiopian Sports Federation managers were advised to consider transformational leadership style dimensions such as inspirational motivation, intellectual simulations and individual considerations in their leadership.